Mechanisms of Surfactin from Bacillus subtilis SF1 against Fusarium foetens: A Novel Pathogen Inducing Potato Wilt - Lin Liu; Xiaofan Jin; Xiuhua Lu; Lizhong Guo; Peiwei Lu; Hao Yu; Beibei Lv (Journal of Fungi, 2023)
Fusarium wilt is a severe and worldwide disease in potato cultivation. In this study, Fusarium foetens was first identified as the pathogen of potato wilt. Bacillus subtilis SF1 has the potential for controlling potato wilt induced by F. foetens, resulting in a mycelium growth inhibition of 52.50 ± 2.59% in vitro and a significant decrease in incidence rate by 45.56% in vivo. This research highlighted the antifungal activity of surfactin from B. subtilis SF1 and attempted to reveal the unknown antifungal mechanisms. Surfactin inhibited F. foetens mycelium growth beyond the concentration of 20 μg/μL. Surfactin-treated mycelium appeared to have morphological malformation. Surfactin enhanced reduced glutathione production and caused the increase in values of the extracellular fluids in OD260 and OD280. Surfactin induced differential protein expression and changed the genes’ transcription levels. Surfactin binds to fungal DNA via groove-binding mode, with a binding constant of Kb 2.97 × 104 M−1. Moreover, B. subtilis SF1 harbored genes encoding plant-promoting determinants, making potato seedlings grow vigorously. The results will help provide a comprehensive understanding of the mechanisms of surfactin against filamentous fungi and the application of surfactin-producing microbial in the biocontrol of plant pathogenic fungi.